Analysis of Corporate Social Responsibility’s Effect on The Value of Mining Companies Moderated by Profitability - Ferdian Agus Iqbal Saputra; Suparlan Pranoto (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
The goal of this study was to determine the influence of “corporate social responsibility disclosure” on “company value of mining company” with “profitability” as a “moderating variable”. This study chose data from “the annual report of mining companies listed on the Indonesia Stock Exchange year 2015-2018”. This study use sample of “26 companies”. Using “purposive sampling technique”, the population of companies according to the minimum number is “18 companies”. This study using “Partial Least Square (PLS)” technique. This study research found that “corporate social responsibility negatively significant effect on company value”, “profitability has a positive effect on company value”. However, “profitability is not able to moderate the influence of Corporate Social Responsibility” to the “value of the company”.